2020
DOI: 10.1093/rpd/ncaa190
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Occupational Radiation Doses of Medical Radiation Workers in Two Community Hospitals

Abstract: The International Commission on Radiological Protection recommends the adoption of the linear, no-threshold model as a predictive risk model for radiation protection purposes since the relationship between low-dose radiation exposure and cancer risk is unclear. Medical radiation workers are subject to occupational exposures and differences in workload, area of work and types of exposure can lead to variations in exposures between different occupational groups. We investigated the occupational exposures of 572 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The occupational radiations effects are usually as a result of short time exposure to high doses of ionizing radiations above the occupational exposure limit (International Atomic Energy cited by Chinangwa et al (3) and Zare and Mortazari (1) . The exposure of radiation workers to ionizing radiations, especially in medical field has increased due to the use of advance technological equipment in the diagnostic radiology and radiotherapy departments (4)(5)(6)(7)(8)(9)(10) . According to UNSCEAR (6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occupational radiations effects are usually as a result of short time exposure to high doses of ionizing radiations above the occupational exposure limit (International Atomic Energy cited by Chinangwa et al (3) and Zare and Mortazari (1) . The exposure of radiation workers to ionizing radiations, especially in medical field has increased due to the use of advance technological equipment in the diagnostic radiology and radiotherapy departments (4)(5)(6)(7)(8)(9)(10) . According to UNSCEAR (6) .…”
Section: Introductionmentioning
confidence: 99%
“…These categories of medical work force are inevitably exposed to long term low-dose ionizing radiation even if they apply the normal personal protective equipment (1,11) . Previous studies have identified the connection between moderate to high-dose exposure to ionizing radiation and the potential of cancer development, such as leukemia, thyroid, lung, colon, breast and bladder cancers (4,12,13) . Although, there were controversial issues regarding the effects of ionizing radiations on humans as noted by Koptar and Garaj-Vrhovire (14) , previous studies on the genetic changes due to ionizing radiation effects reported that the number of chromosomal aberrations in medical personnel working with ionizing radiations was higher than those of the general public (2,15) .…”
Section: Introductionmentioning
confidence: 99%
“…Some physicians receive more extensive external exposure than radiological technologists do. 1 During interventional procedures and fluoroscopic examinations/surgeries, prolonged fluoroscopy is required, physicians and assistants may be positioned close to the patient, and radiation exposure due to scattered radiation may be increased. However, the knowledge and awareness of external radiation protection appear to vary among physicians.…”
Section: Introductionmentioning
confidence: 99%
“…However, the knowledge and awareness of external radiation protection appear to vary among physicians. 1 Radiological technologists typically have acquired sufficient practical knowledge of external radiation protection, and measurement experiments conducted during their time as students may greatly help reduce radiation exposure. Therefore, more practical and effective education on radiation protection might be necessary for medical students.…”
Section: Introductionmentioning
confidence: 99%